How eBay Sellers set 'Buy-it-now' prices - Bringing The Field Into the Lab - Tim Grebe; Radosveta Ivanova-Stenzel; Sabine Kröger (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
In this paper we introduce a new type of experiment that combines the advantages of lab and field experiments. The experiment is conducted in the lab but using an unchanged market environment from the real world. Moreover, a subset of the standard subject pool is used, containing those subjects who have experience in conducting transactions in that market environment. This guarantees the test of the theoretical predictions in a highly controlled environment and at the same time enables not to miss the specific features of economic behavior exhibited in the field. We apply the proposed type of experiment to study seller behavior in online auctions with a Buy-It-Now feature, where early potential bidders have the opportunity to accept a posted price offer from the seller before the start of the auction. Bringing the field into the lab, we invited eBay buyers and sellers into the lab to participate in a series of auctions on the eBay platform. We investigate how traders' experience in a real market environment influences their behavior in the lab and whether abstract lab experiments bias subjects' behavior.
urn:nbn:de:bvb:19-epub-13370-4
Keywords: C72; C91; D44; D82; 330; online auctions; experiments; buyout prices